EXAMPLES OF TYPES OF COMPLEX SENTENCES AND USE IN PRACTICE - Shadiyeva, Shahnoza (Журнал иностранных языков и лингвистики, 2023)
Our article will consider examples of complex types of sentences and examples of their use in practice.